Sociological theory of race and ethnicity: contesting, substituting or complementing? - Chin, Yee Mun; Lee, Yok Fee (Universiti Putra Malaysia Press, 2010)
Issues, related to race and ethnicity, have always attracted attention from many. Throughout the development of sociology, many theories have been developed to explain these phenomena. Most of the time, however, the theories are read as contesting each other. Similarly, argument was laid out as though the theories are contesting to explain the truth of race and ethnicity. Readers have also contributed to the contest. In fact, it is the readers who, most of the time, categorize the theories they read into school of thought and consequently the theories are contesting at least from the readers’ perspective. The theories are also seen as trying to substitute each other, either from the theoreticians’ point of view or from the readers’ point of view. Maybe it is through these contests and the urge to substitute, more and more theories are constructed to explain race and ethnicity. However, instead of contesting and substituting, the theories should also be read as complementing. Sociology is a field that enables society to be understood. Theories related to race and ethnicity should be stitched together to provide the big picture which ultimately leads readers to understand race and ethnicity phenomena. Therefore, this paper focuses on the thoughts of three social analysts, viz., Banton, Geertz and Eriksen. Their contributions to the understanding of race and ethnicity are immense and have never failed to generate discussions and development relating to these areas. By studying and laying out their ideas in complimenting nature, the big picture of what is race and ethnicity could be developed. The big picture is vital and will give significant input to the understanding of issues related to race and ethnicity, particularly in the plural societies such as Malaysia.